Optimising two-stage vacuum heat treatment for a high-strength micro-alloyed steel in railway spring clip application: impact on microstructure and mechanical performance - Lu, Yao; Wang, Jun; Pan, Di; Han, Jian; Zhu, Lisong; Diao, Chenglei; Han, Jingtao; Jiang, Zhengyi (MDPI, 2023)
The heat treatment process is a vital step for manufacturing high-speed railway spring fasteners. In this study, orthogonal experiments were carried out to obtain reliable optimised heat treatment parameters through a streamlined number of experiments. Results revealed that a better comprehensive mechanical performance could be obtained under the following combination of heat treatment parameters: quenching temperature of 850 °C, holding time of 35 min, medium of 12% polyalkylene glycol (PAG) aqueous solution, tempering temperature of 460 °C, and holding time of 60 min. As one of the most important testing criteria, fatigue performance would be improved with increasing strength. Additionally, a high ratio of martensite to ferrite is proven to improve the fatigue limit more significantly. After this heat treatment process, the metallographic microstructure and mechanical properties satisfy the technical requirements for the high-speed railway practical operation. These findings provide a valuable reference for the practical forming process of spring fasteners.
Keywords: Si-Cr spring steel; heat treatment optimisation; microstructure; mechanical property; fatigue performance